A Guide to the Preventive Care of Archaeological Collections. Issue 3 (August 2019) - Meister, Nicolette B.
ABSTRACT: Preservation knowledge is important for those preparing archaeological collections for curation or requesting access to collections for research. Literature about the fields of archaeological conservation and curation is plentiful, but there are scant resources that offer a basic introduction to the knowledge needed to facilitate preservation of and access to archaeological collections. Much of the literature focuses on conservation in the field and in the lab. Archaeological curation standards and the importance of sustainable management of archaeological collections also are well documented. In contrast, this article serves as an introductory guide to preventive care, specifically to the agents of deterioration and the storage considerations that affect preservation of and access to archaeological collections. Collections specialists who work in museums, government repositories, or historical societies, as well as field archaeologists, academic archaeologists teaching and conducting research on collections, and descendant communities in tribal historic preservation offices and other repositories will find this guide useful as a reference and teaching resource. Abstract : El conocimiento de la preservación es muy importante para los que preparan las colecciones arqueológicas para su conservación o para acceder a su investigación. La información sobre los temas de la conservación arqueológica y la preservación es abundante pero hay poco recursos que ofrezcan una introducción básica necesaria para facilitar la preservación y el acceso a las colecciones arqueológicas. La mayoría de los materiales se concentran en la conservación, en la investigación de campo y en el laboratorio. Los estándares de la preservación arqueológica y la importancia del mantenimiento sostenible de las colecciones arqueológicas también están bien documentados. Por el contrario, este artículo sirve de guía introductoria al cuidado preventivo, específicamente contra los agentes de deterioro, y a las maneras de almacenamiento que afectan a la preservación y al acceso a las colecciones arqueológicas. Tanto los especialistas que trabajan en los museos, los depósitos gubernamentales, o las sociedades históricas, como los arqueólogos de campo, los profesores e investigadores universitarios, y los miembros de las comunidades indígenas que trabajan en las oficinas o depósitos de preservación histórica, deben considerar esta guía como referencia y recurso educativo.